Complex skills are required for new primary health care researchers: a training program responds - Terry, Amanda L.; Stewart, Moira; Ashcroft, Rachelle; Brown, Judith B.; Burge, Fred; Haggerty, Jeannie; McWilliam, Carol; Meredith, Leslie; Reid, Graham J.; Thomas, Roanne; Wong, Sabrina T. (Université d'Ottawa | University of Ottawa, 2022)
Abstract Background Current dimensions of the primary health care research (PHC) context, including the need for contextualized research methods to address complex questions, and the co-creation of knowledge through partnerships with stakeholders – require PHC researchers to have a comprehensive set of skills for engaging effectively in high impact research. Main body In 2002 we developed a unique program to respond to these needs - Transdisciplinary Understanding and Training on Research - Primary Health Care (TUTOR-PHC). The program’s goals are to train a cadre of PHC researchers, clinicians, and decision makers in interdisciplinary research to aid them in tackling current and future challenges in PHC and in leading collaborative interdisciplinary research teams. Seven essential educational approaches employed by TUTOR-PHC are described, as well as the principles underlying the curriculum. This program is unique because of its pan-Canadian nature, longevity, and the multiplicity of disciplines represented. Program evaluation results indicate: 1) overall program experiences are very positive; 2) TUTOR-PHC increases trainee interdisciplinary research understanding and activity; and 3) this training assists in developing their interdisciplinary research careers. Taken together, the structure of the program, its content, educational approaches, and principles, represent a complex whole. This complexity parallels that of the PHC research context – a context that requires researchers who are able to respond to multiple challenges. Conclusion We present this description of ways to teach and learn the advanced complex skills necessary for successful PHC researchers with a view to supporting the potential uptake of program components in other settings.